Sosial Media Sebagai Sarana Sosialisasi Politik yang Dilakukan oleh PDIP di Pemilu 2024 - Kisbiyah, Sasqhia Laillyah (UNIVERSITAS SERAMBI MEKKAH, 2025)
With increased internet access, PDIP utilizes platforms such as Facebook, Instagram, TikTok, and Twitter to spread political messages, build a positive image, and interact with voters, especially young voters. While social media offers opportunities to increase political participation, challenges such as the spread of inaccurate information and polarization of opinions are also faced. PDIP showed significant efforts in building interaction with voters through interactive features and creative content, and was more successful compared to Golkar Party and Democratic Party in the 2019 Legislative Election campaign. The success of PDIP's social media strategy can be seen from the increase in public engagement and the strengthening of the party's image, which shows the important role of social media in Indonesian democracy. This research aims to: 1) analyze PDIP's political communication strategy on social media, 2) evaluate the effectiveness of PDIP's social media usage, 3) analyze the role of social media in the context of democracy in Indonesia. The research method used in this research is a case study method with a qualitative descriptive approach. The results of this study are the empowerment of political engagement through social media; identity building and party branding; and challenges faced, such as misinformation and opinion polarization.